Historia wychowania jako pasja i tożsamość naukowa Profesora Wiesława Jamrożka (1954–2021) – w siedemdziesiątą rocznicę urodzin - Brenk, Mikołaj Wojciech; Nowak-Kluczyński, Konrad (Kultura-Społeczeństwo-Edukacja, 2024)
The article presents the figure of an outstanding historian of education who died prematurely on April 2, 2021, head of the Department of History of Education at the Faculty of Educational Studies at Adam Mickiewicz University in Poznań – Professor Wiesław Jamrożek. His interests and research, which were his passion and shaped his scientific identity, centered around the history of educational thought and practice, primarily in the 19th and 20th centuries. They concerned such issues as: theory and methodology of the history of education; creators of the Polish history of education; ideology and educational activity of Polish political and social movements in the 19th and 20th centuries; education of women in the nineteenth and twentieth centuries; Polish pedagogical thought of the nineteenth and twentieth centuries; civic education in Poland in the 19th and 20th centuries; school reforms in Poland (from the 18th to the end of the 20th century); upbringing in the Polish family of the nineteenth and twentieth centuries; history of adult education in Poland in the 19th and 20th centuries; birth and development of social work in Poland.